1984
DOI: 10.1073/pnas.81.7.2026
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of electron transfer between cardiac cytochromes c1 and c.

Abstract: Highly purified cytochrome cl, which consists of only one heme peptide and does not form a stable cl-c complex (cl-H-c complex), was used in studies of electron transfer between cytochromes cl and c. Results show that a stable and ionic-strength-sensitive cl-c complex (i.e., the cl-H-c complex) in the forms of the various oxidation states is not required, in contrast to the current belief of the participation of the complex in the electron transfer between cytochromes cl and c. A minimum mechanism for electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The midpoint potential (+227 mV) for one-band cx is practically the same as that of two-band cx (+225 mV) (Chiang, 1976), and this suggests that the hinge protein does not affect the redox potential (£m) of cytochrome c{. This observation is in agreement with the fact that no direct participation of the hinge protein is observed in the electrontransfer reaction between cytochromes cl and c (Kim et al, 1984) in rapid kinetic studies. Moreover, the enzymatic activity of present cytochrome Ci preparations shows that either one-band or two-band cytochrome c, is active to serve as an electron donor as well as acceptor.…”
Section: Discussionsupporting
confidence: 61%
“…The midpoint potential (+227 mV) for one-band cx is practically the same as that of two-band cx (+225 mV) (Chiang, 1976), and this suggests that the hinge protein does not affect the redox potential (£m) of cytochrome c{. This observation is in agreement with the fact that no direct participation of the hinge protein is observed in the electrontransfer reaction between cytochromes cl and c (Kim et al, 1984) in rapid kinetic studies. Moreover, the enzymatic activity of present cytochrome Ci preparations shows that either one-band or two-band cytochrome c, is active to serve as an electron donor as well as acceptor.…”
Section: Discussionsupporting
confidence: 61%
“…Since the discovery of the hinge protein and its obligatory role for the formation of cytochrome cx-c complex (Kim & King, 1981, 1983Wakabayashi et al, 1982b;, the function of the hinge protein in the mitochondria has remained to be investigated. Studies of structural and func- tional properties of cytochrome q in the presence and absence of the hinge protein (Kim & King, 1987;Kim et al, 1984Kim et al, , 1987a showed that the hinge protein may play a role for stabilizing the structure of cytochrome q. It appears that when the hinge protein is bound to the cytochrome q, the structure of cytochrome q is stabilized and somewhat protected from photoreduction, autoxidation, and other reactions (Kim & King, 1987).…”
Section: Resultsmentioning
confidence: 99%